2016
DOI: 10.1111/gcb.13125
|View full text |Cite
|
Sign up to set email alerts
|

Aggravated phosphorus limitation on biomass production under increasing nitrogen loading: a meta‐analysis

Abstract: Nitrogen (N) and phosphorus (P), either individually or in combination, have been demonstrated to limit biomass production in terrestrial ecosystems. Field studies have been extensively synthesized to assess global patterns of N impacts on terrestrial ecosystem processes. However, to our knowledge, no synthesis has been done so far to reveal global patterns of P impacts on terrestrial ecosystems, especially under different nitrogen (N) levels. Here, we conducted a meta-analysis of impacts of P addition, either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
296
9
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(331 citation statements)
references
References 55 publications
23
296
9
3
Order By: Relevance
“…5b). Li et al (2016) reported that N applications aggravated the P limitations on biomass production. In line with the microbial economic theory, when the P availability was low, the activities of P-acquisition enzymes were higher.…”
Section: Discussionmentioning
confidence: 99%
“…5b). Li et al (2016) reported that N applications aggravated the P limitations on biomass production. In line with the microbial economic theory, when the P availability was low, the activities of P-acquisition enzymes were higher.…”
Section: Discussionmentioning
confidence: 99%
“…; Dijkstra et al . ; Li, Niu & Yu ). Therefore, drought‐induced changes in the N and P cycle are likely to affect plant community composition and productivity, especially in nutrient‐limited systems.…”
Section: Introductionmentioning
confidence: 99%
“…They can limit or co-limit the plant growth (Tripler et al, 2006;Li et al, 2016). Human activities such as fertilization, reclamation and weeding have effects on biogeochemical cycling of P and K. Thereby, it alters the pattern, magnitude and extent of nutrient limitation on land (Marklein and Houlton, 2012).…”
Section: Introductionmentioning
confidence: 99%